We want to find the equivalents from the options to the following equation
![p+q=-48](https://img.qammunity.org/2023/formulas/mathematics/college/7uz3dz24qvsgf9oqxbnu71ss3h5c2r0zun.png)
If we divide both sides by - 3, we're going to have
![\begin{gathered} (p+q)/(-3)=-(48)/(-3) \\ (p+q)/(-3)=16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mq79c8m93fu984fvp9itrgvpihw7rnrqmv.png)
Since this result is different from the first option, the first option is not equivalent to the initial equaiton.
Doing the same for the others, dividing by - 2 we have
![\begin{gathered} (p+q)/(-2)=-(48)/(-2) \\ (p+q)/(-2)=24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wpc7i60l40rdltuh7afvhnlbb9ekob7t5m.png)
dividing by - 12 we have
![\begin{gathered} (p+q)/(-12)=-(48)/(-12) \\ (p+q)/(-12)=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zabszamtvmv2gsv6cyauuojp2ccfa33rul.png)
dividing by 8 we have
![\begin{gathered} (p+q)/(8)=-(48)/(8) \\ (p+q)/(8)=-6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hj6h3g6fr0peznji73552gkwgut8qbz5v3.png)
The only equivalent expression through the options is
![(p+q)/(8)=-6](https://img.qammunity.org/2023/formulas/mathematics/college/yq9scnnultkiq9jeksk0zmm7f2t36qsb3b.png)